The Discursive Topic at the Service of Reading Comprehension in Comics - Bezerra de Sa, Kleiane (2024)
This work, whose theoretical basis is guided by the postulates of Textual Linguistics in its interfaces, with emphasis on studies by Cavalcante and Brito (2022), with perspectives linked to the analysis of texts in use, presents a reflection on the relevance of the discursive topic for the process of reading comprehension. Considered as fundamental criteria for the hierarchization of topics, the properties of centration and organicity, which, according to Jubran et al. (1992) and Sá (2018), prove to be fundamental for the construction of topical tables, which reveal the global organization of the first chapter of the work The Diary of Anne Frank, adapted to the comic book genre. Convinced of this vision, we assume that this framework is fundamental for the establishment of linguistic interfaces that favor the attribution of meanings in the school environment. In order for this objective to be achieved, we initially present the concept of reading comprehension, supported by theorists who deal with this phenomenon, such as Marcuschi (2008) and Oliveira-Nascimento (2014), also highlighting the multimodal character, taking into account the nature of the chosen genre – HQ. We continue the study, detailing the relationship of the discursive topic and its properties with the process of global understanding of the meanings of the opening chapter of the aforementioned comic.